Tertib Potensi Anatomi Manusia Dalam Q.S An-Nahl 78: 16 Perspektif Betrand Russel - Askar Askar (Journal of Islamic Scriptures in Non-Arabic Societies, 2024)
The scientific value of the Qur'an that discusses the creation of humans with the gift of physical completeness is one of the undeniable values. In this case, it is narrated specifically in Q.S an-Nahl 16 (78). The verse is also a scientific legitimization in the realm of modern science that proves the factual values of the Qur'an about the potential that Allah gives to humans in sequence after their release from the womb. Based on this background, the purpose of this research is to prove the existence of isomorphs between the world of al-Qur'anic language and the world of reality. By using Betrand Russel's logical atomism theory analysis to find the isomorph. The result of this research is that there is an isomorph between the world of language in Q.S an-Nahl-16: (78) and the world of reality as proven by modern medical science that the orderly potential of human anatomy is commensurate with what is narrated in Q.S an-Nahl 78: [16].